Capnography use in the critical care setting: why do clinicians fail to implement this safety measure?. (November 2021) - Russotto, Vincenzo; Cook, Tim M.
Summary: Tracheal intubation is among the most frequently performed manoeuvres in the critical care setting, and can be life-saving in critical illness, though also associated with serious adverse events such as oesophageal intubation or tracheal tube obstruction, displacement, or disconnection from the ventilator. A key finding of the 4th National Audit Project (NAP4) was identification of waveform capnography as the single intervention with the highest potential for reducing morbidity and mortality during tracheal intubation and maintenance of an artificial airway. In the INTUBE study, penetration of capnography into ICUs was low, and was not in use in 70% of the episodes of oesophageal intubation. To reduce harm and avoidable death, there is a need for a global initiative to increase access to and use of capnography in ICUs.